Household personal Health Description During The Pandemic of Covid-19 In Kabawo, Muna District - Sitti Nur Arah Like; Hartati Bahar; Rastika Dwiyanti Liaran (Universitas Islam Negeri Alauddin Makassar, 2021)
PHBS is all personal health behavior because of personal awareness so that the family and all its members are able to help themselves in the health sector and get an active role in community activities (Kemenkes RI, 2016). This research contains quantitative research using descriptive methods. The population of this research is housewives in Kabawo District. From the survey data, the number of RTs in Kabawo District spread over 10 villages 1 Kelurahan is 2899 families. With up to 91 families. The method used is Random Sampling / Probability Sampling. Where the techniques and samples that researchers use are random, regardless of the sample on the basis of strata or social status of any way by lot. The result of this study obtained during the covid-19 pandemic, delivery assistance by health workers was 92,3%, Exclusive breastfeeding was 87,9%, The use of healthy latrines was 84,6%, Entirely using clean water was 100%. Washing hands using clean water and soap was 91,2%, Weighing babies and toddlers was 95,6%, Eradicating mosquito larvae was 65.9%, Consuming fruits and vegetables was 98.9%, physical activity was 98.9%, 68,1% were still smoking indoors. Health workers are expected to always improve community health services, especially regarding PHBS activities and families are expected to always increase knowledge so that they are able to carry out daily PHBS